Italian guidelines for the diagnosis and treatment of Paget's disease of bone - G.C. Isaia; G. Bianchi; S. Gonnelli; P. Filipponi; A. Falchetti; M.L. Brandi; P. Bartolazzi; S. Adami; R. Nuti (PAGEPress Publications, 2011)
Paget's disease of bone is a chronic focal abnormality of bone turnover that remains totally asymptomatic over a very long period of time but that eventually ensue in bone pain and skeletal deformities. Although, in the last decade new insights have been obtained on its etiology, this remains largely obscure. Effective medical treatment (based on the use of bisphosphonates) has become available and the diagnostic procedures are now well defined. However, there remains considerable controversy regarding the hierarchy of diagnostic procedures and the medical treatment threshold. In the last few years different institution have published national guidelines, reflecting local national health systems and the available medical treatment. In this review, a working group derived from members of the SIOMMMS has examined the information available regarding the diagnosis and treatment of Paget's disease in order to develop guidelines to assist in the management of this condition. The first draft was then extensively reviewed by experts derived from the most representative scientific societies of rheumatology, internal medicine, and orthopaedic surgery. The document provides the most updated recommendations based primarily on the "evidence-based- medicine" but also on the Italian regulation for the diagnostic procedures and on the available medical treatments.